Predictions of species distributions based only on models estimating future climate change are not reliable - Tsiftsis, Spyros; Štípková, Zuzana; Rejmánek, Marcel; Kindlmann, Pavel (Scientific reports, 2024)
Changes in climate and land use are the most often mentioned factors responsible for the current decline in species diversity. To reduce the effect of these factors, we need reliable predictions of future species distributions. This is usually done by utilizing species distribution models (SDMs) based on expected climate. Here we explore the accuracy of such projections: we use orchid (Orchidaceae) recordings and environmental (mainly climatic) data from the years 1901-1950 in SDMs to predict maps of potential species distributions in 1980-2014. This should enable us to compare the predictions of species distributions in 1980-2014, based on records of species distribution in the years 1901-1950, with real data in the 1980-2014 period. We found that the predictions of the SDMs often differ from reality in this experiment. The results clearly indicate that SDM predictions of future species distributions as a reaction to climate change must be treated with caution.